1998
DOI: 10.1111/j.1432-2277.1998.tb01206.x
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of renal transplant recipients from cyclosporin (Neoral) to tacrolimus (Prograf) for haemolytic uraemic syndrome

Abstract: Five patients with cyclosporin-related haemolytic uraemic syndrome (HUS) following cadaveric renal transplantation were converted from cyclosporin-to tacrolimus-based immunosuppression. All patients had biochemical, haematological and biopsy evidence of HUS at the time of conversion. Four of the patients showed complete resolution of the syndrome within 1 week of conversion with normalisation of haemoglobin, platelets and lactate dehydrogenase levels. In the fifth patient renal function stabilised with slow re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…There is conflicting evidence in the literature as to whether cyclosporine-or tacrolimus-based immunosuppression is less or more likely to cause hemolytic uremic syndrome (HUS). Some support the conversion to tacrolimus as an effective treatment for cyclosporine-related HUS after renal transplantation [5]. Others believe that the side-effect profile of cyclosporine and tacrolimus are indistinguishable when considering post-transplant HUS-like changes [4], and the successful conversion to cyclosporine for tacrolimus-associated HUS has also been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…There is conflicting evidence in the literature as to whether cyclosporine-or tacrolimus-based immunosuppression is less or more likely to cause hemolytic uremic syndrome (HUS). Some support the conversion to tacrolimus as an effective treatment for cyclosporine-related HUS after renal transplantation [5]. Others believe that the side-effect profile of cyclosporine and tacrolimus are indistinguishable when considering post-transplant HUS-like changes [4], and the successful conversion to cyclosporine for tacrolimus-associated HUS has also been reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…In a clinical trial of aspirin, pentoxyfilline, and isradipine in the treatment of post-transplant HUS [MI, all 3 of the patients that were switched to tacrolimus because of the recurrence of HUS after reintroduction of CyA remained off dialysis, albeit with impaired graft function. After switching 5 patients with CyA-induced HUS to tacrolimus, Morris-Stiff et al reported that 4 experienced a rapid resolution of the hemolytic process while the fifth improved after several weeks [8]. However, to date only a small number of patients have been reported as actually benefiting from conversion to tacrolimus in the setting of CyA-induced HUS.…”
Section: Discussionmentioning
confidence: 99%
“…There have been pilot reports to suggest that a reduction in cyclosporin dose (Mourad et al . 1998) or replacing cyclosporin with tacrolimus (Morris‐Stiff et al . 1998) or with mycophenolate mofetil (McGrath & Shehata 2000) resulted in stabilization and, in some cases, improvement of previously declining allograft function.…”
Section: Major Causes Of Renal Allograft Lossmentioning
confidence: 99%
“…(2000) showed that the recurrence rate in non‐nephrectomized patients was higher (92%) than in patients with bilateral nephrectomy (50%). Although changing the maintenance immunosuppression has been successful in the management of de novo , drug‐induced HUS (Morris‐Stiff et al . 1996, 1998; Grupp et al .…”
Section: Major Causes Of Renal Allograft Lossmentioning
confidence: 99%